(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed to shed light on the obstacles to employing technology-based audit techniques and their impact on developing the performance of internal audit devices at the University of Fallujah. The research problem was that there was a deficiency in the employment and use of advanced technology in implementing internal audit activities and procedures. To achieve this goal, a field study was carried out at the University of Fallujah and the questionnaire was used to collect primary data related to the subject of research and process this data using the statistical program (SPSS). The research concluded a set of results, the most important of which is the acceptance of the vocabulary of the research sample for most of the elements of the questionnaire list, where the value of Value 0.000 for most of the questions, as well as the combined variables of the questions of obstacles to employment (CAATTS) Q1ALL and its impact on the development of internal audit devices ALL Q2), and based on the above, it can accept the imposition of research, so there is a negative impact of obstacles to employment (CAATTS) on the development of performing internal audit bodies. The research also found that there is a lack of interest in using these Techniques in the work by the audit bodies operating at the university. The research recommended a set of recommendations, the most important of which is that the university should prepare all technical requirements to move from internal audit in its traditional way to auditing considering advanced technology. As well as the scientific and practical qualification of workers in audit by involving them in training programs to keep pace with the requirements of adopting and employing these technologies in all internal audit activities and procedures to achieve the maximum benefit from them. Keywords: internal audit, technology-based audit techniques.